Small-scale garment producers‘ application of circular economy practices in the Cape Coast - Abubakari, Umar (University of Cape Coast, 2024)
This study aimed to assess the awareness, understanding, and application of Circular Economy (CE) practices among small-scale garment producers in the Cape Coast Metropolis, Ghana. It was guided by three theoretical frameworks: the Diffusion of Innovation Theory, the Theory of Planned Behaviour, and the Resource-Based View of the Firm, which collectively informed the analysis of factors influencing CE practice adoption. The study employed a mixed-methods approach using a Sequential Exploratory Design, carried out in two phases. In the first phase, involved qualitative data collection. Twenty (20) participants were purposively selected for semi-structured interviews, and an additional seven (7) participants took part in a focus group discussion, making a total of 27 qualitative participants. The thematic analysis technique was applied to identify emerging themes and perspectives from the qualitative responses. The second phase quantitative data to enrich the qualitative findings. The quantitative data were gathered from 140 randomly selected participants using structured questionnaires. These questionnaires collected data on the level of awareness, influencing factors, perceived benefits, and challenges associated with CE models. The data were analyzed using descriptive statistics and structural equation modeling to uncover patterns and relationships. Key findings revealed that while there is a moderate level of awareness of CE concepts, significant challenges such as limited access to technology, inadequate expertise, and poor infrastructure hinder adoption. Nevertheless, small-scale producers recognize several benefits of CE models, especially in terms of cost savings, reduced material usage, and environmental advantages. The study concludes that the integration of CE practices is promising but requires systemic support. It recommends that government agencies, financial institutions, and stakeholders provide targeted interventions such as capacity-building workshops, grants, subsidies, and low-interest loans to enable small-scale garment producers to transition sustainably into circular practices.
xii,197p;, ill
Keywords: small scale garment producers circular